Fertigation of Vitis vinifera L. cv. Bukettraube/110 Richter on a Sandy Soil - Conradie, W.J.; Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
Fertigation and conventional fertilisation were compared for a Bukettraube vineyard on sandy soil in the arid Olifants River region of South Africa. During the first stage (four years) of the experiment, all treatments received 120 kg N.ha-1.yr-1 and 80 kg K.ha-1.yr·I. The first treatment (C120) entailed conventional (broadcast) fertiliser applications at three-week intervals the second (F120) was fertigated at three-week invervals, while the third (1120) was fertigated twice per week. Yield and shoot growths were not affected significantly, indicating that conventional fertilisation was just as effective as fertigation (C120 vs F120). Furthermore, the fact that the application of N in regular, small increments (1120) held no advantage over larger applications at longer intervals (Fl20) suggested that leaching of nutrients did not occur, probably as a result of well-managed irrigation practices. During the second stage of the experiment (three years) 1120 was discontinued, while Cl20 and Fl20 were compared with a third treatment (F80), fertigated at 80 kg N.ha-1.yr-1 and 60 kg K.ha-1.yr-1. Irrigation for these three treatments was scheduled by means of tensionmeters and soil was replenished to field water capacity twice per week. In a fourth treatment (D120), fertigated at 120 kg N.ha-1.yr-1 and 80 kg K.ha-1.yr-1 , deficit irrigation was practised, with monthly water application being approximately 30 mm less in comparison to the other treatments. In general, no differences were observed between F120 and C120, while cane mass and yield for both these treatments were higher than those of F80 and D120. This indicated that 80 kg N.ha-1.yr-1 was insufficient and that suboptimal irrigation can have a marked negative effect on vines growing in a low-potential soil. The results suggested that K was still adequately supplied in the case of F80, and that reduced performance could be ascribed to N deficiency only. Annual application of 80 kg K.ha-1.yr-1 by means of fertigation (F120 and D120) was needlessly excessive and impaired Mg uptake. Fertigation showed no positive or negative effects on wine quality overall.